Tool Wear Condition Monitoring using Slip Ring and Accelerometer System in Milling AISI P20 Tool Steel / Wan Nuha Wan Mansor...[et al.] - Wan Mansor, Wan Nuha; Md Tahir, Nurul Hidayah; Abd Ghani, Jaharah; Che Haron, Che Hassan; Nuawi, Mohd Zaki; Rizal, Muhamad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Vibration is among the common tool parameters used in tool condition monitoring (TCM). TCM plays a crucial role as the control and management of processes. There is an increased need to produce machines that are more efficient and that incur minimum maintenance costs. Tool failure and wear greatly reduce the cost while constantly maintaining the quality of production. Various monitoring systems have been developed by past researchers aimed at better configurability and flexibility. In this work, a simple and reliable method for data transmission in rotating machines using a slip ring and accelerometer system was applied and tested. During the testing, the vibrations at the tool tip were measured using an accelerometer. The results showed that the vibrations increased by an increase in the tool wear. However, in relation to several cutting parameters, the vibrations increased when the feed rate was high but decreased when a lower value of the axial depth of cut, ae, was used. In conclusion, the relationship between tool wear evolution and vibration signals can be established using the cutting tool vibration signals.